Identification of teaching competencies among TVET instructors towards the realization of 4th industrial revolution - Minghat, Asnul Dahar; A., Ana; Jamaludin, Suhaida; Mustakim, Siti Salina; Shumov, Petr V. (National Academy of Sciences of the Republic of Kazakhstan, 2020)
Developing in the field of technical and vocational education and training (TVET) continuously is a challenge for the career of TVET instructors to maintain their success. It is very necessary to encourage teachers for making progress in teaching and efficient learning. It is also of great importance to have the ability to understand the skills that are required by their job needs. From a broader perspective, those trained through the processes of vocational learning will meet the labor market's skill needs. In the aftermath of this study, teaching should be focused on the profile of the teaching competencies of the TVET-instructor. The Delphi approach was the compilation, interpretation, and evaluation of qualitative data in this study. Qualitative data was collected from the 11 expert panels of TVET, based on their skills and experience. The quantitative data were collected using the questionnaire set by the researcher based on the competence of the teaching elements proposed by the Delphi system. The random sampling technique was used as respondents from five selected public skills training institutions in the selection of 106 mechanical engineering and manufacturing technology instructors. Research findings have shown that the dimension of teaching technique is important for teaching profiles of competencies at the instructors of the Public Skills Training Institution TVET. In the context of mastering the competence for the implementation of the 4th Industrial Revolution, the study also found that the use of project-based learning methods is ranked as the lesser in teaching methodology as it should be reinforced at five selected training institutions for public skills.